Digital Education on YouTube: An Analytical Study of Arabic Language Learning Content on the "Arab Podcasts" Channel on YouTube - Destia Nikhlatunnuha; Muhammad Zaenuri; Saiful Islam; Amar bin Muhammad bin Ahmed (Al-Muyassar: Journal of Arabic Education, 2025)
Digital learning makes it easier to access learning, digital learning can be done on various platforms, one of which is youtube. The purpose of this research is to describe the learning content of listening to Arabic on the Arabic podcast youtube channel. The approach used in this study is a qualitative approach with the content analysis method. The primary data in this study is in the form of listening learning content on the Arabic podcast youtube channel, while the secondary data in this study are books and scientific papers that discuss learning listening skills and digital learning. The data collection technique in this study uses Observation and Documentation Techniques, the Data Analysis Technique in this study uses Qualitative Analysis, namely data reduction, data presentation, and conclusion drawn. The video on the Arabic podcast youtube channel shows the use of expository learning strategies and uses a combination of two learning methods, namely the lecture learning method and the translated learning method. The material used comes from the book al kalam 100 conversations in Arabic volume 2, and is delivered in 2 languages. In addition, the media and video communication aspects selected on the ara podcast youtube channel also show the use of six principles that must be considered in the creation of media elements. Judging from the analysis of the content of the content, it allows the Arabic Podcasts channel to be used as an example or reference for content developers in creating content to learn Arabic listening skills and to acquire listening skills in students.Keywords: Listening Skills; Digital learning; YouTube مستخلص البحثيسهل التعلم الرقمي وصول التعلم، ويمكن إجراء التعلم الرقمي على منصات مختل?ة، أحدها يوتيوب. الغرض من هذا البحث هو وص? المحتوى التعليمي للاستماع إلى اللغة العربية على قناة البودكاست العربي على يوتيوب. النهج المستخدم ?ي هذا البحث هو نهج نوعي مع طريقة تحليل المحتوى. البيانات الأولية ?ي هذا البحث هي محتوى تعليمي للاستماع على قناة البودكاست العربي على يوتيوب، بينما البيانات الثانوية ?ي هذا البحث هي كتب وأوراق علمية تناقش تعلم مهارات الاستماع والتعلم الرقمي. تستخدم تقنية جمع البيانات ?ي هذا البحث تقنيات الملاحظة والتوثيق، وتستخدم تقنية تحليل البيانات ?ي هذا البحث التحليل النوعي، وهي تقليل البيانات وعرض البيانات واستنتاجها. ال?يديو على قناة البودكاست العربي على يوتيوب يدل على استخدام استراتيجيات التعلم الت?سيري ويستخدم الجماع من طريقتين للتعلم، وهما طريقة تعلم المحاضرات وطريقة تعلم الترجمة. المواد المستخدمة أ?خذت من كتاب الكلام 100 محادثة باللغة العربية المجلد 2، ويتم تقديمها بلغتين. بالإضا?ة إلى ذلك، تظهر جوانب الاتصال الإعلامي وال?يديو المختارة على قناة البودكاست العربي على يوتيوب أيضا استخدام ستة مبادئ يجب مراعاتها عند إنشاء عناصر الوسائط. ومبدأ التخصيص. انطلاقا من تحليل محتوى المحتوى، ?إنه يسمح باستخدام قناة البودكاست العربي كمثال أو مرجع لمطوري المحتوى ?ي إنشاء محتوى لتعلم مهارات الاستماع باللغة العربية واكتساب مهارات الاستماع للطلاب.